Socio-Economic Factors Influencing Smallholder Farmer Household Food Security in Bomet County, Kenya - Koskei, Fredrick K.; Gor, Christopher O.; Okora, Julius (International Journal of Recent Research in Interdisciplinary Sciences (IJRRIS), 2018)
Majority of farmers live in rural areas and contribute immensely to economy and wealth creation among the rural population, however they are faced with myriad of problems Including food insecurity. Even though they participate in food production most of them are food insecure. The objectives of the study included to:(1) examine the socio-economic profile of small holder farmers, (2) determine the socio-economic factors influencing food security among smallholder farmers and (3) assess household food security status of smallholder farmers. The study utilized both primary and secondary data sources. Purposive sampling was used to select 384 respondents who were interviewed using structured questionnaires. To establish food security status of farming households in the study area, Food Insecurity Experience Scale (FIES) which is a food security measurement scale was used to determine food security status of each household. Logit regression model was used to analyze the influence of socio-economic factors on farm household food security. Data was summarized and presented through descriptive statistics using SPSS version 20.0 software. Results showed that only 20.7% of the respondents were food secured compared 79.3% who were food insecure. Additionally, seven variables positively influenced food security of the household: age, land size, gender, educational level, civil status, household incomes, price of major agricultural commodities and access to credit. Apart from gender and price of major agricultural commodities other variables positively and significantly influenced food security. Based on research findings the main recommendations of the study include: family planning would be necessary to reduce high food insecurity; Efficient land use, soil conservation and modern farming technologies be adopted to improve food security; and policies that encourage youth participation in agriculture should be developed and adopted.
Keywords: Bomet County; Food security; Logit regression; Socio - economic